2020
DOI: 10.1007/s11920-020-01191-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-Suicidal Self-Injury and Eating Disordered Behaviors: An Update on What We Do and Do Not Know

Abstract: Purpose of Review The current report aims to summarize recent advances about the relationship between non-suicidal self-injury (NSSI) and eating disordered (ED) behaviors and highlights meaningful directions for future research. Recent Findings While there is solid evidence indicating a robust cross-sectional association between NSSI and ED behaviors, emerging evidence suggests that the temporal relationship between these behaviors may be bidirectional. Shared functions and risk factors may explain why these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 120 publications
(153 reference statements)
0
33
0
1
Order By: Relevance
“…NSSI, binge eating, binge drinking, cannabis use, and risky sexual behaviours) in a sample of Italian community-dwelling students and to define different groups of adolescents, based on their engaging in types of maladaptive behaviours. Considering that it is well-established that NSSI and eating disordered behaviours frequently co-occur [ 26 ] we expected that in our sample NSSI and binge eating were distinguished by other types of maladaptive behaviours. Secondly, we aimed to evaluate the associations between adolescent groups engaging in different clusters of maladaptive behaviours and ED, depression, anxiety, impulsivity, trauma experiences and BPD related personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…NSSI, binge eating, binge drinking, cannabis use, and risky sexual behaviours) in a sample of Italian community-dwelling students and to define different groups of adolescents, based on their engaging in types of maladaptive behaviours. Considering that it is well-established that NSSI and eating disordered behaviours frequently co-occur [ 26 ] we expected that in our sample NSSI and binge eating were distinguished by other types of maladaptive behaviours. Secondly, we aimed to evaluate the associations between adolescent groups engaging in different clusters of maladaptive behaviours and ED, depression, anxiety, impulsivity, trauma experiences and BPD related personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…EDs and NSSI share several risk factors and functions [ 18 ]. Both are self-destructive, have the onset and peak incidence during youth, are more prevalent in females, and share underlying functions of affect regulation and increased mortality risk by suicide [ 2 , 19 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also observed an increased risk of NSSI thoughts, urges, and behavior in the presence of high self-criticism and negative repetitive thinking [ 39 , 40 ], or low momentary self-efficacy to resist NSSI [ 35 ]. Despite this knowledge, future research is needed to clarify the relative importance of these situational, emotional, and cognitive factors at each stage of the NSSI process and their specificity in predicting NSSI compared to co-occurring behaviors (eg, eating disorder behaviors, suicidal thoughts) [ 27 , 41 ]. Worth mentioning in this context is that real-time monitoring also provides a unique opportunity to clarify the relationship with these comorbid behaviors in daily life [ 42 ], thereby offering meaningful information to further diagnostic understanding of NSSI.…”
Section: Opening the Black Box Of Daily Life Brings Exciting New Opportunities For Science And Practicementioning
confidence: 99%